Pengaruh Penggunaan Media TV Sekolah dan Metode Belajar Contextual Teaching And Learning (CTL) Terhadap Kemampuan Kognitif Anak - Harahap, Ernawati; watini, Sri (Jurnal Inovasi Pendidikan MH Thamrin, 2022)
This study aims to reveal the effect of using school television media and Contextual Teaching and Learning (Ctl) learning methods on children's cognitive abilities. This research is a quantitative research. The sampling technique used was Cluster Random Sampling. The research sample amounted to 22 students in group B. The test results of the research instrument showed that the reliability of the cognitive ability instrument was 0.921. The data analysis technique used is simple regression analysis. The conclusions of this study are 1) the cognitive ability of students who are given school TV has a positive effect on the cognitive abilities of students who are given the CTL method; 2) The cognitive ability of students given the school TV affects the cognitive abilities of students given the CTL method; 3) the coefficient of determination R Square = 0.150, which means that 15.0% of the variation of the variable cognitive ability of students given school TV can be influenced by the variable of cognitive ability of students given the CTL method.Keywords: Cognitive Ability, School TV, Contextual Teaching Learning